2009 11th Electronics Packaging Technology Conference 2009
DOI: 10.1109/eptc.2009.5416460
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic interference suppression and simultaneous switching noise mitigation in system on package using a lowpass filter structure with embedded capacitor

Abstract: System on package (SOP) is an emerging technology, and provides an implementation options for system with small size, especially for mixed-signal systems. However, in such a compact package, noise generated by the digital chip can be easily coupled to the RF IC, and degrade the sensitivity of RF signal. In this paper, a simple and efficient multi-order lowpass filter for EMI and SSN suppression in system on package is implemented with embedded capacitor material. It has good performance in noise isolation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…EMI is an undesirable disturbance that occurs due to switching and affects an electrical circuit [15]. EMI is categorized into radiated and conducted EMI.…”
Section: Acronym Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMI is an undesirable disturbance that occurs due to switching and affects an electrical circuit [15]. EMI is categorized into radiated and conducted EMI.…”
Section: Acronym Descriptionmentioning
confidence: 99%
“…Chenbin Tao et al [13] and Wu et al [14] introduced solution to reduce CM EMI in SMPS with hybrid filter (HEF). Li et al [15] used the system on package (SOP) Multi-order low pass filter for EMI and simultaneous switching noise suppression. It is concluded that the performance of noise isolation is achieved at a higher level with a smaller size.…”
Section: ) Emi Filter Designmentioning
confidence: 99%